2015
DOI: 10.1097/ijg.0000000000000222
|View full text |Cite
|
Sign up to set email alerts
|

Incremental Healthcare Service Utilization for Open-angle Glaucoma

Abstract: We concluded that subjects with OAG had significantly higher utilization of all healthcare services than comparison subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…The total cost of medical treatment would have been higher except for a decrease in the unit cost of the most commonly prescribed glaucoma medication, latanoprost, due to the expiry of its patent in January 2012. 12 The actual costs of managing glaucoma in the National Health System, however, are likely to be much higher with the increased number of referrals, monitoring for an increased number of patients, and surgery for selected patients, 31 32 which have not been calculated in this study. It is likely that variations in practice exist, which may impede the efficient allocation of resources for glaucoma treatment.…”
Section: Discussionmentioning
confidence: 91%
“…The total cost of medical treatment would have been higher except for a decrease in the unit cost of the most commonly prescribed glaucoma medication, latanoprost, due to the expiry of its patent in January 2012. 12 The actual costs of managing glaucoma in the National Health System, however, are likely to be much higher with the increased number of referrals, monitoring for an increased number of patients, and surgery for selected patients, 31 32 which have not been calculated in this study. It is likely that variations in practice exist, which may impede the efficient allocation of resources for glaucoma treatment.…”
Section: Discussionmentioning
confidence: 91%
“…The National Longitudinal Health Insurance Database 2000 (LHID2000) contains data on a group of individuals selected randomly from among 1 million participants in the NHIRD, which represents about 4.5% of the Taiwanese population. 12 We utilized the LHID2000 database to gather information on patient demographics, including identification number, sex, age, and diagnostic data. Diseases were defined using to the International Classification of Diseases, 9th Revision, Clinical Modification (ICD-9-CM).…”
Section: Database and Study Samplementioning
confidence: 99%
“…Glaucoma patients created two-fold higher costs utilizing healthcare facilities than nonglaucoma patients in Taiwan. Outpatient visits and inpatient days were included in these costs [18].…”
Section: Resultsmentioning
confidence: 99%
“…A group in Taiwan compared healthcare utilization by glaucoma patients and nonglaucoma patients in Taiwan during a 1 year follow-up and compared total healthcare costs of both groups [18]. The study found that two-fold higher total costs were generated by greater healthcare utilization by glaucoma patients.…”
Section: Healthcare Utilization By Glaucoma Patientsmentioning
confidence: 99%